Which pesticides are contaminating a brazilian soils? (Research, Society and Development, 2020)
Pesticides play an important role within society, but their overuse can cause problems for the health of the environment. Among these problems, soil contamination by pesticides has been little discussed, a matter of concern, since soil quality is directly related to ecological functioning, primary production and human health. Soil contamination by pesticides depends on different factors such as soil, soil and substance properties. The use of pesticides has been the target of different worldwide discussions, however, these discussions in the Brazilian scenario are even more necessary due to the vast consumption and application of these substances in the country. This review presents a critical view of soil contamination by pesticides within the Brazilian territory using as tools the calculation of the risk quotient and comparison between the reference values for Canadian and Brazilian soil. It is noteworthy that only 12 Brazilian federative units had data available on pesticide concentrations in Brazilian real soils (Amazonas, Bahia, Maranhão, Mato Grosso, Minas Gerais, Para, Paraná, Rondonia, Rio de Janeiro, Rio Grande do Sul, Santa Catarina, Sao Paulo). The most detected pesticides in soil and in higher concentrations were Dichlorodiphenyltrichloroethane, Hexachlorocyclohexane and Hexachlorobenzene. In general, the study sites had particular exposure scenarios and were unrelated to the current use of pesticides in the country. In this context, the importance of further studies on pesticide residues in Brazilian soils is emphasized.